PERANAN PEMERINTAH DESA DALAM PENANGGULANGAN KEMISKINAN (Studi Kasus Desa Sejahtera Kecamatan Bulango Selatan Kabupaten Bone Bolango) - Joice Machmud; Abdul Gafur Patuti (Universitas Muhammadiyah Gorontalo, 2022)
Poverty reduction is still a priority for the government, especially the village government. Various poverty reduction programs are still being carried out by the government, therefore the role of the village government is always a concern. This study aims to determine the role of the village government by taking a case study of the Sejahtera Village, Bulango Selatan District, Bone Bolango Regency. This study used a qualitative approach by using informants as sources to answer the research objectives through interviews.The results of the study concluded that the role of the Government in poverty alleviation in the Prosperous Village has been implemented through various poverty reduction programs, namely the construction of latrines, construction of habitable houses and the provision of empowerment assistance in the agricultural sector. This role can be seen from four aspects or indicators, namely; aspects of the people who take part in social interactions, aspects of behavior that appear in interactions, aspects of people's position in behavior, and aspects of the relationship between people and contributing behaviors.